Systematic Review of Progressive Resistance Strength Training in Older Adults - Nancy K. Latham; Derrick Bennett; Clare Stretton; Craig S. Anderson (2004)
Background. The aim of this systematic review was to quantify the effectiveness of progressive resistance strength training (PRT) to reduce physical disability in older people. Methods. Randomized controlled trials were identified from searches of relevant databases and study reference lists and contacts with researchers. Two reviewers independently screened the trials for eligibility, rated their quality, and extracted data. Only randomized controlled trials utilizing PRT as the primary intervention in participants, whose group mean age was 60 years or older, were included. Data were pooled using fixed or random effect models to produce weighted mean differences (WMD) and 95% confidence intervals (CI). Standardized mean differences (SMD) were calculated when different units of measurement were used for the outcome of interest. Results. 62 trials (n = 3674) compared PRT with a control group. 14 trials had data available to allow pooling of disability outcomes. Most trials were of poor quality. PRT showed a strong positive effect on strength, although there was significant heterogeneity (41 trials [n = 1955], SMD 0.68; 95% confidence interval [CI] 0.52, 0.84). A modest effect was found on some measures of functional limitations such as gait speed (14 trials [n = 798], WMD 0.07 meters per second; 95% CI 0.04, 0.09). No evidence of an effect was found for physical disability (10 trials [n = 722], SMD 0.01; 95% CI −0.14, 0.16). Adverse events were poorly investigated, but occurred in most studies where they were defined and prospectively monitored. Conclusions. PRT results in improvements to muscle strength and some aspects of functional limitation, such as gait speed, in older adults. However, based on current data, the effect of PRT on physical disability remains unclear. Further, due to the poor reporting of adverse events in trials, it is difficult to evaluate the risks associated with PRT.